The Combined Effects of ENSO and Solar Activity on Mid-Winter Precipitation Anomalies Over Southern China - Wang, Ruili; Ma, Hedi; Xiao, Ziniu; Li, Xing; Gao, Chujie; Gao, Yuan; Lai, Anwei; Li, Xiao (Frontiers in Earth Science, 2021)
Both the El Niño-Southern Oscillation (ENSO) and the 11-year solar cycle had been identified as important factors that may influence the wintertime southern China precipitation (SCP). However, the interactions between these two factors remain less noticed. In this study, the combined effects of the ENSO and the solar activity on mid-winter (January) SCP are investigated using observational and reanalysis data. Results suggest that both the ENSO and the solar activity are positively correlated with the SCP, although exhibiting distinct spatial patterns. Under different combinations of the ENSO and solar phases, the SCP anomalies show superposition of these two factors to some extent. Generally, the ENSO-related SCP anomalies tend to be enhanced (disturbed) when the ENSO and the solar activity are in-phase (out-of-phase). But this solar modulation effect appears more clear and significant under cold ENSO (cENSO) phase rather than under warm ENSO (wENSO) phase. Further analysis suggests, during the wENSO phase, solar influences on the Northern Hemisphere circulation are generally weak with little significance. In contrast, during the cENSO phase, the solar effect resembles the positive phase of the Arctic Oscillation but with an evident zonal asymmetric component. Its manifestation over the Asia-Pacific domain features by negative geopotential height anomaly over the West Asia and positive geopotential height anomaly over the East Asian coast, a pattern that is favorable for the SCP, thus causing a significant solar modulation on the cENSO-related precipitation anomalies. Further, the potential physical causes of solar effects on circulation are also discussed. Our results highlight the importance of considering solar cycle phase when ENSO is used to predict the East Asian winter climate.